Multi-dimensional reference-dependent preferences in sealed-bid auctions – How (most) laboratory experiments differ from the field - Lange, Andreas; Ratan, Anmol (Games and economic behavior, 2010)
We study bidding behavior in first- and second-price sealed-bid auctions with loss-averse agents. Our model predicts overbidding in first-price induced-value auctions consistent with evidence from most laboratory experiments. Substantially different bidding behavior could result in commodity auctions where money and auction item are consumed along different dimensions of the consumption space. Differences also result in second-price auctions. Our study thereby indicates that transferring qualitative behavioral findings from induced-value laboratory experiments to the field may be problematic if subjects are loss-averse.